Вспененные шлаки, получение и применение - Кравченко, В. П.; Ганкевич, В. Ф.; Киба, В. Я. (My University, 2015)
У статті описані деякі способи отримання спінених шлаків. Наведено мікрошліфи спі-нених шлаків (термозит, штучна пемза та ін). Матеріали зі спіненого доменного шлаку від-повідають вимогам для житлового будівництва по звукоізоляції, теплопровідності, пожеж-ній безпеці. Мікроструктура спіненого шлаку містить пухирці повітря, які забезпечують спіненому шлаку достатню легкість і низьку теплопровідність, що робить їх гарним мате-ріалом для селищного будівництва.

В статье описаны некоторые способы получения вспененных шлаков. Приведены мик-рошлифы вспененных шлаков (термозит, искусственная пемза и др.). Материалы из вспе-ненного доменного шлака отвечают требованиям для жилищного строительства по звуко-изоляции, теплопроводности, пожаробезопасности. Микроструктура вспененного шлака содержит пузырьки воздуха, которые обеспечивают вспененному шлаку достаточную лег-кость и низкую теплопроводность, что делает их хорошим материалом для поселкового строительства.

The receipt and use of foamed blast furnace slag is one of the links in the complex chain of pro-cessing metallurgical wastes – slags. Granulated slag is obtained in the form of a particulate material by rapid cooling of molten slag. When producing foamed slag (thermoset, artificial pumice, etc.) get larger grain, acting on the molten slag in a limited amount of water. There are different ways to obtain a foaming slag, which provide a product of sufficiently good quality. Microstructure of foamed slag, unlike granulated slag, contains air bubbles that provide a foamed slag are sufficiently clear and low thermal conductivity that provides high consumer qualities, as a building material for the erection of cottages and town-ship construction. The construction of residential buildings made of slag bricks and concrete provides high-quality performance of works on extensive use of blast-furnace slags of different types – granu-lar, lumpy and foam.
Keywords: получение вспененных шлаков; микрошлиф вспененных шлаков; микроструктура вспененного шлака